Basque nationalists in Navarre: a long road to success - I. V. Krivushin (Ибероамериканские тетради, 2022)
The aim of the article is to examine the reasons for the Basque nationalists’ improving electoral performance in Navarre in the late 2000–2010s. The author identifies the main stages of the historical development of Basque nationalism in Navarre and its confrontation with various forms of local regionalism (Fuerism, Carlism, and Navarrism) from the beginning of the 20th century up to the present, as well as the features of its evolution in comparison with the evolution of nationalism in other Basque territories. The analysis of electoral statistics and opinion polls shows that, in the post-Franco period, the traditional centrist and Catholic version of Basque nationalism, represented by the Basque Nationalist Party, was pushed back by its left and secular version (“Herri Batasuna”, “Batzarre”, “Aralar”, etc.) and that, in the last decade, Basque nationalists managed to significantly expand their influence among social groups that do not favour separatist claims and do not share nationalist feelings. On the one hand, the success of this expansion was due to the new electoral tactics of the Basque nationalists (formation of two coalitions – left and center-left), and, on the other, to the growing discontent of voters towards the central and regional authorities in the context of the financial crisis of 2008 – 2014 and the gradual increase in the popularity of the Basque language and strengthening of the Basque identity in Navarre. The rising separatist movement in Navarre, together with the growing popularity of secessionism in Galicia, threatens to increase the number of separatist-leaning regions in Spain and poses a serious challenge to the Spanish “State of Autonomous Communities.”